DIMENSIONS OF PATERNALISTIC LEADERSHIP AND EMPLOYEE OUTCOMES IN SMALL THAI FIRMS - Duangta Duangekanong, Duangta; Duangekanong, Somsit; John, Varughese K; Wichayachakorn, Asawin; Vikitset, Nithiphong (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
The purpose of this study is to examine the effect of paternalistic leadership dimensions (authoritarian, benevolent, and moral) on employee outcomes in small Thai firms. Outcomes examined include two intermediate outcomes (organizational commitment and job satisfaction) and one further outcome, resulting from organizational commitment and job satisfaction, which was self-reported in-role job performance. Paternalistic leadership was studied because of its cultural consonance in Thailand and its status as a frequently observed leadership approach. Data was collected from a sample of small firm employees in Thailand (n = 218). The study used a structural equation modeling (SEM)-based approach to examine the proposed relationships. The results showed that while benevolent and moral leadership had positive effects on employee organizational commitment and job satisfaction, authoritarian leadership had a weak negative effect on these two outcomes. Organizational commitment and job satisfaction had positive effects on job performance, with a stronger effect seen for organizational commitment. The implication of these findings is that some aspects of paternalistic leadership are effective for small firms in a Thai cultural context, but that authoritarian models of paternalistic leadership should not take precedence. This is useful information for small firm leaders as well as policymakers focusing on SME development.